Peran Dukungan Sosial pada Penyesuaian Akademik Mahasiswa Baru dengan Resiliensi Akademik sebagai Mediator - Sari, Citra Ayu Kumala; Zaini, Arina Husna (Universitas Trunojoyo Madura, 2024)
The transition of life and academic environment from high school to university is a massive change for new students. Therefore, high academic adjustment is needed so that students can complete their educational journey in college. This research aims to determine the mediating role of academic resilience in the relationship between social support and academic adjustment of new students. The sampling technique used was cluster random sampling with a research sample of 323 new students. Data collection techniques used the Multidimensional Scale of Perceived Social Support (MSPSS), Academic Adjustment Scale (AAS) and Resilience Academic Scale questionnaires with reliability values above 0.7. The results of analysis using SEM AMOS found that resilience completely mediates the relationship between social support and academic adjustment. This shows that students who receive social support will be able to adapt in the academic field, only if they have good resilience. This study provides an understanding of the importance of social support given to new students so that students can survive and get through the difficult times in their first year so that they can adapt to the academic demands at university.